Ocena korytarzowej metody uprawy dębu (Quercus sp.) na przykładzie obiektów badawczych w nadleśnictwach Mircze i Kościan - Paluch, Rafał; Gil, Wojciech (Leśne Prace Badawcze, 2018)
The corridor method of oak ( Quercus sp) cultivation is an old, forgotten silvicultural method. It was developed around the turn of the 19th and 20th century on the south-eastern borders of Poland (Podole, Wołyń) and Russia and made use of other species such as hornbeam, linden and birch as a cover for oak, which is a tree species sensitive to frosts. The nowadays recurring phenomenon of oak disease initiated a search for silvicultural alternatives and thus the usefulness of reviving the corridor method for oak regeneration was investigated by examining existing tree stands established in this way. Our research plots were located in five young stands and two in mature as well as old stands. In the stands of the 2nd and 3rd age classes, the density of oaks was observed to be 1500–3500/ha, which accounted for 30–50%. The density of oak in old stands (7th age class) was similar to model-predicted values. Furthermore, the corridor method gave very good production results as exemplified by the oak stands growing on the fresh broadleaved site, which had a very high stand quality index. In addition, the species composition was observed to diversify throughout these oak stands’ development, thus supporting arguments for the conservation and preservation of oak-hornbeam forests. To summarise, the prerequisites for the success of the corridor method are systematic cuts of young stands (forest cultures and thickets) to inhibit the growth of accompanying undesired species and limiting the number of grazing animals.